Controversies over the discussions around the new Fund for Maintenance and Development of Basic Education and Appreciation of Education Workers (Fundeb), Brazil - Francisco José da Silva (Fineduca, 2022)
This paper aims to discuss controversies around the new Fundeb, which was approved in August 2020 through Constitutional Amendment No. 108. It is assumed that the origin of the policy of funds in education and of Fundeb itself goes back to the disputes fought since the Education Pioneers’ National Movement in the 1930s, extending until at least 1960, being taken up by social movements since 1990. In methodological terms, bibliographic and documentary research was used, focusing on articles, legal frameworks concerning public funds, revised versions of the Constitutional Amendment No. 15, 2015, and Fineduca’s manifestations about the new Fundeb from February to July 2020. The main findings are as follows: The Union should invest more resources in basic education without compromising other educational actions; and the need to carry out researches that take into consideration deeper historical aspects connected to the public policy education funding.